Teachers and Staff's Perceptions of an Antiracist and Dual Language Bilingual Program at an Urban School - (:unkn) unknown (My University, 2013)
This study was conducted in an urban school in the Midwestern region of the United States that implements a two-way bilingual (English- Spanish) and an antiracist program. The focus of the study was to learn about the teachers and staff's perceptions of these two programs. While the study revealed challenges in both programs that can weaken their implementation; most teachers and staff at the school shared a common understanding about antiracist principles. However the school's dual language program was subtractive to minority students (Valenzuela, 1999) since the quality of the Spanish language and culture offered at the school was limited. Highlighting the majority language over the minority language and depriving minority students from developing their language and culture, resulted in the school's perpetration of linguistic racism, contradicting the antiracist values they aim to promote through their antiracist program.   These findings based on the school's teachers and staff insight cam help analyze and improve both programs in the school, as well as antiracist and dual language programs in general.
Keywords: Antiracist Education; Bilingual Programs; Dual-language; Teachers Perceptions